Polygonal cracking associated to vertical and subvertical fracture surfaces in granite (La Pedriza del Manzanares, Spain): considerations for a morphological classification - García-Rodríguez, M.; Gómez Heras, M.; Álvarez de Buergo, M.; Fort, R.; Aroztegui, J. (Journal of Iberian Geology, 2015)
The area known as Pedriza de Manzanares forms part of the Upper Manzanares River Basin and of the recently (June 2013) listed Sierra de Guardarrama National Park, located in the Spanish province of Madrid. The region is home to Late Palaeozoic granites characteristic of the Spanish Central Systam, which were intruded during the Variscan Orogeny and uplifted to their present position during the Alpine Orogeny. Previous studies of polygonal cracking in granite suggest several possible control mechanisms. Some authors contend that weathering patterns are governed by internal geodynamic factors, such as the final stages of magmatic consolidation or differential movements in fault planes as a result of their structural position. Others claim that climate-related external factors, specifically insolation rates and thermal differences, can explain the predominance of a given orientation in such patterns. The present paper is a study of the effect of case hardening on polygonal cracking, and the role of variables such as temperature and rock surface hardness in granite weathering. It also aims to establish a general systematic classification for polygonal cracking, focusing particularly on the cracking associated with the sub-vertical planes of fracture at Pedriza de Manzanares. The morphometric parameters associated with cracks and fractures, including strike and dip, are analysed, along with the height of occurrence and shape of polygonal cracks.
Keywords: Polygonal cracking; case hardening; granite weathering; Sierra de Guardarrama National Park